Забруднення водойм дендропарку “Олександрія” та його вплив на стан рослинності - Pleskach, L.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
The investigations were discovered, that waters of ponds of Western beam of the dendropark Olexandria are very much polluted Cr6+, oilproducts and NH4+. Bottom deposits of ponds – heavy metals, especially Cr, Mn and oilproducts. The worse of state of vegetation is result of pollution of park water objects.